(untitled) (Medicine Today, 2017)
Surgical site infection (SSI) is defined as infection at surgical site within 01 month after surgery (or within a year in case of implant). Surgical-site infection requires microbial contamination of the surgical wound to occur. LA provides considerable benefits over OA, including a shorter length of hospital stay, less postoperative pain, earlier postoperative recovery, and a lower complication rate. This was a prospective observational study conducted inpatient department of Chittagong Medical College Hospital and private hospitals and clinics in Chittagong city. The patients were interviewed face to face by the researcher for the purpose of collection of data and were examined by the researcher for certain signs recorded in the fixed protocol. Collected data was classified, edited, coded and entered into the computer for statistical analysis by using SPSS-22. Out of 200 cases mean age was found 33.76 ± 23.35 years in OA group and 32.21 ± 16.51 years in LA group. Male was found 58% in OA group and 53% in LA group. Female was found 42% and 47% in OA and LA group respectively. Mean operative time was found 41.2±8.5 minutes in OA group and 49.3±8.9 minutes in LA group. Alternate pathology were more frequently detected in LA due to wide area of vision. Superficial incisional SSI was found 10% in OA group and 5% in LA group. Deep incisional SSI was found 2% in OA group and 2% in LA group. Organ/space SSI was 2% and 3% in OA group and LA group respectively. Staphylococcus aureus is the commonest organism isolated form the surgical wounds from 41.34% followed by Pseudomonas 21.26%, no growth 11.1%, E.coli 9.6%, others 9.4%, Klebsiella 7.0%. Laparoscopic appendectomy was better than open appendectomy with respect to wound infection rate, postoperative pain, postoperative hospital stay and return to normal activities. Medicine Today 2017 Vol.29(1): 6-11